Neurofilament light chain in spinal fluid and plasma in multiple system atrophy: a prospective, longitudinal biomarker study - Singer, Wolfgang; Schmeichel, Ann M.; Sletten, David M.; Gehrking, Tonette L.; Gehrking, Jade A.; Trejo-Lopez, Jorge; Suarez, Mariana D.; Anderson, Jennifer K.; Bass, Pamela H.; Lesnick, Timothy G.; Low, Phillip A. (Clinical autonomic research, 2023)
Purpose There is a critical need for reliable diagnostic biomarkers as well as surrogate markers of disease progression in multiple system atrophy (MSA). Neurofilament light chain (NfL) has been reported to potentially meet those needs. We therefore sought to explore the value of NfL in plasma (NfL-p) in contrast to cerebrospinal fluid (NfL-c) as a diagnostic marker of MSA, and to assess NfL-p and NfL-c as markers of clinical disease progression. Methods Well-characterized patients with early MSA ( n = 32), Parkinson’s disease (PD; n = 21), and matched controls (CON; n = 15) were enrolled in a prospective, longitudinal study of synucleinopathies with serial annual evaluations. NfL was measured using a high-sensitivity immunoassay, and findings were assessed by disease category and relationship with clinical measures of disease progression. Results Measurements of NfL-c were highly reproducible across immunoassay platforms (Pearson, r = 0.99), while correlation between NfL-c and -p was only moderate ( r = 0.66). NfL was significantly higher in MSA compared with CON and PD; the separation was essentially perfect for NfL-c, but there was overlap, particularly with PD, for NfL-p. While clinical measures of disease severity progressively increased over time, NfL-c and -p remained at stable elevated levels within subjects across serial measurements. Neither change in NfL nor baseline NfL were significantly associated with changes in clinical markers of disease severity. Conclusions These findings confirm NfL-c as a faithful diagnostic marker of MSA, while NfL-p showed less robust diagnostic value. The significant NfL elevation in MSA was found to be remarkably stable over time and was not predictive of clinical disease progression.